Creep flow and fracture behavior of the oxygen-enriched alpha phase in zirconium alloys. (May 2016) - Chosson, R.; Gourgues-Lorenzon, A.F.; Vandenberghe, V.; Brachet, J.C.; Crépin, J.
Abstract: During hypothetical Loss-Of-Coolant-Accident (LOCA) scenario, zirconium alloy fuel cladding tubes are exposed to internal pressure and high temperature oxidation, so that an oxygen-stabilized α(O) phase, forms from the outer surface of the cladding, under the zirconia oxide layer. The high-temperature viscoplastic flow and fracture behavior of the α(O) phase were characterized through axial creep tests performed under vacuum, on representative model materials containing 10–30 at.% of oxygen. Creep strengthening and ductile-to-brittle transition were quantified as a function of oxygen content and test temperature, and modeled into viscoplastic flow constitutive equations and an empirical fracture criterion. Graphical abstract: